Makna Pendidikan Agama Hindu dalam Pementasan Wayang Lemah Pada Karya Ngenteg Linggih Merajan Pratisentana Dalem Tarukan - I Ketut Sudarsana; Ni Kadek Lia Candrawati (Purwadita : Jurnal Agama dan Budaya, 2023)
The procession of staging lemah puppet has many components which are symbols of Hinduism and have the educational value that can be used as a guide for Hindus. This study aims to determine the performance of lemah puppet in the Karya Ngenteg Linggih Merajan Pratisentana Dalem Tarukan, Denpasar Pakraman Village, from the perspective of Hindu religious education. This type of research is qualitative research with field research and library research. The informant determination technique used was purposive sampling. The data sources used are primary and secondary data sources. Data collection techniques in this study are observation, interviews, literature study, and documentation. The results of the study show that the procession of the performance of the lemah puppet in the Karya Ngenteg Linggih in Merajan Pratisentana Dalem Tarukan, Denpasar Pakraman Village, is a stage consisting of pre-staging, beginning, primary, and final activities, in the various stages carried out, it is contained in the religious system in the form of symbols, ceremonies, and spells that have been arranged according to the standard in the dharma pewayangan. From this procession, the functions of the performance of the lemah puppets emerged, which consisted of religious functions, purification, social solidarity, and aesthetic functions. The performance of lemah puppet is also full of the meanings of Hindu religious education. The meaning of education contained in the performance of lemah puppet is the meaning of spiritual education, kinship, event skills, and cultural arts.